Applying a combined geospatial and farm scale model to identify suitable locations for mussel farming. (July 2020) - von Thenen, Miriam; Maar, Marie; Hansen, Henning Sten; Friedland, René; Schiele, Kerstin S.
Abstract: Mussel farming has increasingly come into focus as a potential mitigation measure for fish farms and eutrophication, in addition to being a food source. This study presents a GIS-based suitability analysis combined with a farm scale model to identify appropriate mussel farming sites. The sites are investigated in terms of potential mussel harvest, nutrient removal, and effects on water transparency. The model is applied to the south-western Baltic Sea. The identified suitable area is about 5–8% of the case study extent. The model shows that elevated chlorophyll levels stimulate mussel growth and that upon mussel harvest, nutrients can be removed. A single mussel farm cannot compensate for all nutrients emitted by a fish farm, but it can increase water transparency up to at least 200 m from the farm. Potential nutrient removal and water transparency increases are essential criteria for site selection in eutrophic seas, such as the Baltic Sea. Graphical abstract: Unlabelled Image Highlights: Mussel farming may be an internal measurement to mitigate eutrophication To identify suitable sites, a combined GIS analysis and farm scale model is applied The GIS analysis identifies spatial constraints in the south-western Baltic Sea The farm scale model estimates nutrient removal and impact on water transparency These parameters should be part of mussel farm site selection in eutrophic areas